IMPACT DE LA CHASSE NOCTURNE DU GIBIER SUR LA DISPONIBILITE DE VIANDE DE BROUSSE CHEZ LES TURUMBU, TERRITOIRE D’ISANGI, REPUBLIQUE DEMOCRATIQUE DU CONGO - Itindi, Jérôme Waliala Apataki; Joël Bondekwe Baruti,; Taylor Athongo,; Jean Akaluko Towowo ,; Pierre Basuli Wemaeli , (IJRDO - Journal of Social Science and Humanities Research, 2019)
In all the Africa, hunt and the wild fauna use were complete part of the life style of the majority of the peoples once.  Hunt was governed traditionally by social practices, norms, sanctions and taboos that granted the respect and the protection required to the wild fauna. In the majority of the cultures, some species were considered like sacred totems and were classified only in particular opportunities.  This reflection is suitable to the contribution of the advancement of the debate on the lasting development founded on the exploitation rational of the natural resources in Turumbu middle through the sensitization of the autochthonous peoples on the valorization of the alternative activities.  To answer this preoccupation, the present reflection intends to present the perception of the nocturnal hunt first at the Turumbus before scrutinizing the consequences bound to this practice for to tackle on the strategies the resort this community to fight against this practice.